2003
DOI: 10.1002/cc.129
|View full text |Cite
|
Sign up to set email alerts
|

From the foundations up: Contexts for change in community college advancement

Abstract: Unlike past fiscal crises and retrenchment, current changes in the funding of public higher education could precipitate fundamental changes in colleges and universities. Community colleges might be well positioned to thrive in such turbulent times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The model includes elements from which all types of community college foundations, from those that are underdeveloped to those that are well-run, could benefit. Researchers have found that with traditional sources of funding continuing to dwindle for institutions of higher education (Bass, 2003;Hearn, 2003;Phillippe & Sullivan, 2005), many institutions have had to shift their focus to include private fundraising (Anderson, 2005;Cohen & Brawer, 2003;Hearn, 2003). As a result, many institutions have made great fundraising progress in the 21st century (Council for Aid to Education, 2007).…”
Section: Implications For Practicementioning
confidence: 98%
See 2 more Smart Citations
“…The model includes elements from which all types of community college foundations, from those that are underdeveloped to those that are well-run, could benefit. Researchers have found that with traditional sources of funding continuing to dwindle for institutions of higher education (Bass, 2003;Hearn, 2003;Phillippe & Sullivan, 2005), many institutions have had to shift their focus to include private fundraising (Anderson, 2005;Cohen & Brawer, 2003;Hearn, 2003). As a result, many institutions have made great fundraising progress in the 21st century (Council for Aid to Education, 2007).…”
Section: Implications For Practicementioning
confidence: 98%
“…Funding for these expenses is typically not available from the community colleges due to dwindling monies from traditional sources of revenue (Bass, 2003;Hearn, 2003;Phillippe & Sullivan, 2005).…”
Section: Operating Budgetsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously receiving most of their funding from their states, community colleges now operate with decreased state funding, increased student tuition, and minimal local funding (Bass, 2003;Phillippe & Sullivan, 2005). These cuts continue to present serious challenges for community colleges.…”
mentioning
confidence: 98%
“…These cuts continue to present serious challenges for community colleges. To alleviate the adverse impact of diminishing traditional sources of funding, community colleges are relying more and more on their foundations to seek additional sources of funding (Anderson, 2004=2005;Cohen & Brawer, 2003;Hearn, 2003) such as philanthropic donors (Bass, 2003). Many of these foundations are less than 40 years old (Angel & Gares, 1981) and differ greatly from their four-year counterparts with educational foundations that are decades older.…”
mentioning
confidence: 98%